Understand the customer experience of luxury brands at before purchase stage and investigate the way to enhance this experience. - Chou, Yi Hsuan (2014)
The importance of customer experience is enhancing significantly, especially on luxury brand. Customer experiences can be discussed from the decision making process model. In this paper, it will focus on luxury brands and investigate relative attributes which will influence customer experience at the before purchase stage. There are some elements like personal attributes and environmental atmosphere. The information from 2 focus groups was used for data analysis in the paper. The results indicate that these elements can have lead to customer experiences. Furthermore, focus group interview findings show that five store factors including layout, general interior, innovation, product display and signs and human variables have positive effect on consumer experience of luxury brand at the before purchase stage. On the other hand, personal attributes show that goal, memory, involvement and attitude also contribute to increase customer experiences. This paper also mentioned about managerial implication, research limitation, and provided suggestions for further research.